SIMBA: Tendon-Driven Modular Continuum Arm with Soft Reconfigurable Gripper - Mishra, Anand Kumar; Del Dottore, Emanuela; Sadeghi, Ali; Mondini, Alessio; Mazzolai, Barbara (Frontiers in Robotics and AI, 2017)
In this paper we describe the conceptual design and implementation of the SIMBA manipulator, designed and developed for participating in the RoboSoft Grand Challenge 2016. In our novel design we have proposed: 1) a modular continuum arm with independent actuation units for each module, to increase maintainability; 2) a soft reconfigurable hand, for a better adaptation of the fingers to objects of different shapes and size; 3) a moving base for increasing the workspace. We used a hybrid approach in designing and manufacturing by integrating soft and hard components, in both materials and actuation, providing high lateral stiffness in the arm through flat springs, soft joints in fingers for more compliancy and tendon-motor actuation mechanism providing flexibility but at the same time precision and speed. The SIMBA manipulator has demonstrated excellent grasping and manipulation capabilities by being able to grasp objects with different fragility, geometry and size; and by lifting objects with up to 2Kg of weight it demonstrate also to be robust and reliable. The experimental results pointed out that our design and approach can lead to the realization of robots able to act in unknown and unstructured environments in synergy with humans, for a variety of applications where compliancy is fundamental, preserving robustness and safety.